2004
DOI: 10.1530/eje.0.1510747
|View full text |Cite
|
Sign up to set email alerts
|

Changes of diurnal rhythm and levels of total and free testosterone secretion from pre to late puberty in boys: testis size of 3 ml is a transition stage to puberty

Abstract: Objective: To establish levels for comparison for 24-h total and free serum testosterone in prepubertal boys and throughout pubertal development. Design: The study subjects were 55 healthy boys, aged 5.0-18.6 years, who underwent serial sampling one or more times during their pubertal development. Methods: Testicular volumes were determined by orchidometer. Serum testosterone was measured by a modified RIA (detection limit, 0.03 nmol/l). Free testosterone was calculated (calc-FT) using a formula derived from t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
76
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(82 citation statements)
references
References 40 publications
5
76
0
1
Order By: Relevance
“…Largo and Prader' s landmark 1983 14 longitudinal study on white Swiss boys proposed testicular volume of 3 mL as the most accurate sign of central pubertal takeoff based on their earlier work, later confirmed by the Cincinnati 15 and Swedish studies. 16 Boys in the Swiss study were a mean age of 11.2 at genital stage 2 and 11.8 at a testicular volume of 3 mL. The study by Biro et al 15 is the only US puberty study that reported testicular volumes.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Largo and Prader' s landmark 1983 14 longitudinal study on white Swiss boys proposed testicular volume of 3 mL as the most accurate sign of central pubertal takeoff based on their earlier work, later confirmed by the Cincinnati 15 and Swedish studies. 16 Boys in the Swiss study were a mean age of 11.2 at genital stage 2 and 11.8 at a testicular volume of 3 mL. The study by Biro et al 15 is the only US puberty study that reported testicular volumes.…”
Section: Discussionmentioning
confidence: 89%
“…Data on Cincinnati boys 15 and Swedish boys 16 show that the transition from 2 to 3 mL indicates pubertal take-off. White boys in this study reached a mean age of transition to 3 mL at 9.95 years, African American boys at 9.71, and Hispanic boys at 9.63, with no significant difference (P = .11).…”
Section: Figurementioning
confidence: 99%
“…Por ejemplo en Estados Unidos de Norteamérica (Tabla 3) en población hispánica se encontró una edad de inicio de pubertad de 10 años en varones evaluados por inspección genital 13 y los cambios testiculares fueron más precoces que los observados por inspección. A pesar de lo anterior, esta investigación evaluó crecimiento testicular ≥ a 3 ml, lo que destaca la diferencia de criterios y dificultades en comparar los diferentes estudios 14,15 . Sin embargo, cuando se analizó el aumento de VT ≥ 4 cc esta población mostró el inicio a los 11 años.…”
Section: Discussionunclassified
“…This may be due to potentially interfering substances, particularly cross-reacting water-soluble steroid conjugates, binding proteins (especially SHBG), and non-specific binding (NSB). Concentrations of SHBG are known to be high in prepubertal children (median 92 nmol/l) (12,13) and postmenopausal women (mean 103 nmol/l) (14), and in combination with the 5000-15 000 times lower 17b-estradiol concentrations it is a challenge to quantify accurate concentrations of 17b-estradiol. In this study, we show that the 17b-estradiol calibrators included in the Spectria kit on average contain four times lower SHBG concentrations when compared with that in children's sera.…”
Section: Discussionmentioning
confidence: 99%